EFEKTIVITAS STRATEGI MIND MAPPING PADA MATERI SISTEM PENCERNAAN MANUSIA DALAM PEMBELAJARAN IPA DI MASA PANDEMI COVID-19 - Lucky Arvinni Wijaya; Elok Sudibyo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This research was conducted with the aim of describing the effectiveness of mind mapping strategy in science learning during the pandemic. The research design used One Shot Case Study. This research was conducted on 31 students from two classes, there are class VIII A and class VIII C at SMP Negeri 2 Mojosari. The results of data collection were analyzed using the average value of the posttest questions and the results of the scores in class VIII A were 81 and VIII C was 88 so that the average value of the two classes was 84.5. The results of the scores to achieve the criteria for the conceptual understanding indicator based on the aspect of understanding such as the indicator interpreting the highest value of 58 and the lowest of 50, exemplifying the highest value of 59 and the lowest of 56, classifying the highest value of 54 and the lowest of 53, summarizing the highest value of 61 and the lowest is 56, inferring the highest value is 48 and the lowest is 46, comparing the highest value of 51 and the lowest of 45 and explaining the highest value of 64 and the lowest of 57 and the percentage value of completeness that is seen based on the calculation of the percentage of indicators of understanding the concept of class VIII A a percentage of 52% and class VIII C obtained a percentage value of 56% with the completeness category quite effective. The completeness value of science subjects is 73, therefore grades VIII A and VIII C have exceeded the standard of KKM values and it is also proven that the mind mapping strategy is effective enough to be carried out in distance or online learning during the Covid-19 pandemic. The conclusion from this study is that the mind mapping strategy is very effective in learning during the Covid-19 pandemic on the material of the human digestive system.